Pengaruh Motivasi Berprestasi dan Kebiasaan Belajar terhadap Keberhasilan Belajar Mahasiswa Program Studi Bimbingan dan Konseling Tahun Akademis 2011/2012 - Mudjijanti, Fransisca (Widya Warta, 2013)
The success in learning does not depend merely on the brilliance of the brain. There are many other factors which affect the success intended. Attitudes, habits, and skills in learning contribute substantially  in determining the success of the students. Therefore, the students should strive to have  good attitudes, habits,  and skills in learning, and try to avoid or overcome obstacles in learning. A student who applies an effective method of learning may gain a higher achievement compared to those who apply ineffective methods. In fact, motivation also influences the success in learning. Highly motivated individuals usually pay their attention to personal achievement, not to prestige, obtained either with or without any help of others. High motivation has great affects on the individuals to achieve the desired performance. The  analysis  of  correlation  coefficient  showed  that  there  was  a  tight  correlation between      motivation and habits in learning with the success of the students of Guidance and Counseling as indicated by the correlation value of 0. 426. The analysis of determination coefficient revealed that the success of the students of Guidance and Counseling was influenced by variables of  motivation and  habits in learning by 18.2%. The t-test proved that the first hypothesis, which reads " otivation affects the success of the students of Guidance and Counseling" was accepted , and the second hypothesis, which reads" habits in learning affect the success of the students of Guidance and Counseling" was rejected. The F test showed that the major hypothesis which reads “motivation and habits in learning affect the students’ success" was accepted.